Quantitative Research in Education: Philosophy, Uses and Limitations - Rauteda, Khem Raj (Papanda Publisher, 2025)
Conventionally, the quantitative research approach is believed to be used in natural science to experiment with phenomena and test theories and hypothesis. However, it has been practiced by researchers in social science and education at present. The study aims to critically analyze the philosophical stances of quantitative research and to explore the uses and limitations of quantitative research methods in education. I used document analysis as a research method where I collected previously published books, journal articles, and book chapters in the related field, read them, explored the required information from the materials, analyzed them critically, and made the arguments in different themes. The study revealed that quantitative research is based on the positivist paradigm which believes in objectivity, and experimental reality. It further showed that quantitative research is significant in the field of education to test the methods, and teaching-learning theories, to see the cause-and-effect relationship, and to see the causal relationship between the variables. Moreover, it shows that quantitative research is significant to explore the results that can be generalized in a large population. Additionally, the study explored that quantitative research has several issues such as negligence on educational complexities, sampling bias, issues of validity, and generalizability, and ethical issues related to consent, confidentiality, anonymity, sampling, data collection, interpretation, and reporting. It suggests that researchers in education should incorporate the qualitative method and mixed-method research to address diversity, emotion, experience, and multiple realities.